Peran Dosen Dalam Meningkatkan Nilai-Nilai Berkarakter Di Era Revolusi Industri 4.0 - Dewi Endah Fajariana (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential to have spiritual spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation and state. The research design of this scientific work is qualitative and the target and target of this study is the even semester semester STKIP Panca Sakti Bekasi students with a population of 73 people with saturated sampling that is the entire population used as a sample. Which are the targets and targets of this research, namely students in semester 2, semester 4, semester 6A and semester 6B at the STKIP. The role of the Lecturer to students is by growing the love of the motherland through the nature of defending the State.Participation in defending the country for students can be manifested in various activities. The activity in question is intracuricular and extracurricular activities. Through intracuricular activities, students participate in teaching and learning activities in an orderly, disciplined, obedient to school rules already means preparing themselves as the next generation of intelligent and broad-minded nation. Whereas through extracurricular activities can be realized through scouting activities, nature lovers, sports activities, arts, journalism, teenage scientific work, Indonesian Red Cross, student regiments, anti-drug movements, and others. At this mature age, lecturers are required to play a professional role in carrying out their duties in accordance with applicable laws, namely having a social role in the life of society and the state.